W. J. T. Mitchell's Core Ideas on Image and Text - Susanti, Anastasia Jessica Adinda (Jurnal Filsafat "WISDOM", 2025)
This study examines the important ideas of W.J.T. Mitchell’s theories on image and text. The link between word and image has long been a topic of controversy, from Plato's differentiation between "word" and "image" in ancient Greece to the current debates around image-text interaction in AI technology. The study of images and words, or iconology, frequently leads to discussions about how politics, power, reality, and value are related to images and texts. An eminent iconologist, William John Thomas (W. J. T.) Mitchell coined the phrase "pictorial turn" in 1994 to counter the linguistic movement, which had replaced the importance of images with language. Mitchell’s theory of image and text covers important ideas such as the pictorial turn, metapicture, biopicture, and the idea of image and text as mixed media. His work covers a broad range of subjects, from media aesthetics, visual culture, iconology, to image theory. The necessity to examine Mitchell's contributions to the study of image and text is expanding as his theories become more and more well-known worldwide.The purpose of this essay is to examine Mitchell's concepts, paying special attention to the dynamic interaction between word and image. In summary, Mitchell's "pictorial turn" positions pictures as dynamic entities and emphasizes their importance in scholarly discourse and culture. His work addresses unresolved questions concerning the nature of images, their connection to language, their historical relevance, and their effect on viewers. Mitchell challenges the traditional understanding of images as passive objects by introducing the idea of "metapictures"—images that reflect on their own nature—and transforming images into active subjects that are capable of self-theorization. The distinction between text and image is blurred by this reinterpretation, which also promotes a greater understanding of the nuanced ways that visual culture influences and reflects the human condition.